Module Structure on Effect Algebras - Saidi Goraghani, Simin; Borzooei, Rajab Ali (Bulletin of the Section of Logic, 2020)
In this paper, by considering the notions of effect algebra and product effect algebra, we define the concept of effect module. Then we investigate some properties of effect modules, and we present some examples on them. Finally, we introduce some topologies on effect modules.